اللغة العربية: تحليل لغوي نقدي لتعريفات اللغويين العرب - Kamila, Fariha Zahra; Musa, Muhammad Ali; Khumairoh, Siti Aisyatul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Arabic holds a strategic role in the field of linguistics and the construction of civilization. This study employs a qualitative approach based on literature review to analyze the perspectives of three linguistic scholars on the Arabic language: Ibn Jinni, Musthafa Al-Ghulayaini, and Imam Bawani. The analysis reveals that Ibn Jinni defines language as sound used by a community to convey specific intentions, emphasizing its social and phonetic aspects. Musthafa Al-Ghulayaini views language as a complex instrument of communication that requires an understanding of grammatical structure and contextual usage. Imam Bawani, on the other hand, asserts that Arabic was born, developed, and spread in the Arab region and holds a special status in Islamic tradition. All three agree that language functions as a fundamental medium of communication for humanity and highlight the importance of Arabic in the Islamic context.